COVID-19 Presented With Deep Vein Thrombosis: An Unusual Presenting - Lotfollah Davoodi MD; Hamed Jafarpour MD; Morteza Taghavi MD; Alireza Razavi MD (SAGE Publishing, 2020)
On December 31, 2019, the World Health Organization was informed of a cluster of cases of pneumonia of unknown cause detected in Wuhan City, Hubei Province, China. The pneumonia was caused by a virus called SARS-Cov-2 (severe acute respiratory syndrome coronavirus 2), which was later named coronavirus infectious disease 2019 (COVID-19). The symptoms most commonly reported by patients affected by COVID-19 include fever, dry cough, and shortness of breath. In this report, we present a case of a 57-year-old woman who presented to the clinic's infectious department with swelling, pain, warmth, and redness in the left leg who was treated with therapeutic heparin. There were no typical and distinguished symptoms of COVID-19, and she had no risk factor for deep vein thrombosis. Then chest X-ray revealed bilateral patchy ground-glass opacity, and computed tomography angiography was performed to rule out pulmonary thromboembolism, which showed no evidence of thrombosis. Left lower limb venous color Doppler ultrasound revealed dilatation and thrombosis in the external iliac and left iliac veins up to the level of the bifurcation of the common iliac veins, as well as thrombosis to the superficial and small saphenous veins. Because of ground-glass opacity and lymphopenia, nasal swabs were used for sampling, and SARS-CoV-2 nucleic acid was detected by reverse transcription polymerase chain reaction (RT-PCR). This case aims to arouse the medical staff's awareness of deep vein thrombosis as a clinical symptom of COVID-19 even if the patient has no typical symptoms of COVID-19.